Factors Influencing Newborn Care Practices Among Mothers In The Jirapa Municipality of the Upper West Region of Ghana. - Zolko-Ere, R.N. (University of Ghana, 2018)
Every year, four million infants die within their first month of life, representing nearly 40 per-cent of all deaths of children under age 5 globally. Also, over 99% of all newborn deaths occurs in developing countries with about two-thirds of them taking place in the Sub-Saharan Africa and Asia. Therefore, understanding factors that influence newborn care practices in the home environment where most newborns are cared for is essential in order to develop appropriate approaches and interventions for reducing neonatal mortality. This study sought to explore the factors that influence newborn care practices among mothers in the Jirapa Municipality of the Upper West Region of Ghana. Methods: A cross-sectional study using mixed methods was used to evaluate newborn care practices. Quantitative data was collected from 341 postnatal mothers and analyzed using STATA 15.0 while qualitative data was collected from focus group discussions and analyzed with the help of NVIVO. A chi-square association and simple/multiple logistic regression were used to determine the association and extent to which socio-demographic factors and knowledge level influence the practice of newborn care among mothers and the cultural beliefs that influence newborn care practices. Results: Findings from the quantitative analysis showed that, mothers who received information regarding newborn care practices from health professionals only, had 2.39 times (AOR=2.39, 95% CI=1.32-4.33, p-value=0.004) the odds of having a good practice of newborn care compared to mothers with multiple sources of information. Mothers who received monthly income (100-200GHC) had 4.62 times (AOR=4.62, 95% CI=1.38-15.47, p-value 0.013) the odds of a good practice of newborn care compared to mothers who received no monthly income. Eighty-three percent (83%) of mothers who were living together with their partners as marital status category (AOR=0.17, 95% CI= 0.03-0.88, p-value=0.035) were less the odds of having a good practice of newborn care when compared to mothers who were never-married. More so, mothers with adequate knowledge of newborn care practices had 4.05 times (AOR=4.05, 95% CI=1.54-10.65, p-value=0.005) the odds of having a good practice of newborn care compared to mothers with inadequate knowledge. There exist cultural beliefs that influence mothers‘ practices of newborn care, such as the belief that a newborn baby will die if not fed, welcomed and invited with a drop of water, the belief that the umbilical cord will not heal fast if shea butter was not continuously applied and the belief that without the local substance ―kpallah‖ in the newborn baby‘s eyes, the eyeballs would not be white and beautiful. Conclusion: Increased education by health care providers on having health professionals as the main source of information regarding newborn care practices contributes greatly to good newborn care practices among mothers. Access to income has great impact on good practices of newborn care. Again, routine and continuous education of mothers by health care professionals on newborn care practices increases mothers‘ knowledge level which eventually reflects on good newborn care practices. Also, there are some cultural beliefs and practices that are detrimental to the health and survival of newborns hence should be discouraged by all.
Thesis (MPh)
Keywords: Sub-Saharan; Africa and Asia; Quantitative; Upper West; Newborn Care; Logistic; Marital status category; Municipality